2016
DOI: 10.1016/j.ajpath.2015.10.031
|View full text |Cite
|
Sign up to set email alerts
|

The Eyes Absent Proteins in Developmental and Pathological Angiogenesis

Abstract: Management of neoangiogenesis remains a high-value therapeutic goal. A recently uncovered association between the DNA damage repair pathway and pathological angiogenesis could open previously unexplored possibilities for intervention. An attractive and novel target is the Eyes absent (EYA) tyrosine phosphatase, which plays a critical role in the repair versus apoptosis decision after DNA damage. This study examines the role of EYA in the postnatal development of the retinal vasculature and under conditions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
36
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 34 publications
2
36
0
Order By: Relevance
“…7a, d) possibly indicating ongoing DNA damage and repair in surviving PAECs through non-EYA3-dependent mechanisms. These trends are similar to those obtained in previous studies with other disease models where BZ treatment reduces the levels of DDR foci 24,29 .
Fig. 7EYA-PTP inhibition reduces markers of DNA damage and repair.
…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…7a, d) possibly indicating ongoing DNA damage and repair in surviving PAECs through non-EYA3-dependent mechanisms. These trends are similar to those obtained in previous studies with other disease models where BZ treatment reduces the levels of DDR foci 24,29 .
Fig. 7EYA-PTP inhibition reduces markers of DNA damage and repair.
…”
Section: Resultssupporting
confidence: 90%
“…2f, g). To test the hypothesis that the EYA PTP activity might contribute to the ability of PAH-PASMC to survive DNA damage we used the previously characterized small molecule inhibitor benzarone (BZ) 24,2729 . In the presence of BZ, PAH-PASMC survival after exposure to H 2 O 2 was reduced to levels comparable to that of normal PASMC (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the case of tumor cells, the hypoxic environment can affect stromal cell behavior [ 116 ]. Endothelial cells are known to increase proliferation in response to a hypoxic environment and to activate a DDR signaling cascade similar to that described for tumor cells [ 117 119 ]. Accumulating evidence suggests that immune cell infiltration into the hypoxic tumor microenvironment increases angiogenesis and tumor metastasis [ 6 , 120 ].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Recently, accumulating evidence has shown that EYA functions in the mediation of DNA repair, cell apoptosis, angiogenesis and tumor growth. [9][10][11][12][13] EYA4 was found to be epigenetically silenced and was reported to function as a potential tumor suppressor gene in various types of common human cancers such as esophageal adenocarcinoma, 14 breast cancer, 15 lung cancer 16 as well as in oral dysplasia. 17 In contrast, EYA4 has been reported to play an oncogenic role in peripheral nerve sheath tumors and breast cancer.…”
mentioning
confidence: 99%